Virgilio Txerribuztangoerrekan (I. "Bukoliken" eta "Georgiken" euskal itzulpenak) - Ruiz, Iñigo (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1995)
The translations of the ancient classics start to appear in the Basque literature at the beginning of the XIXth century: their goal is not, by any means, to make them accessible to a public that would be unable to read them otherwise, but rather to serve as an exercise to the translators as well as to the readers and, at the same time, to dignify the Basque literature with works of universal value that, moreover, would not imply any submission to any national culture. The fact that Virgil has always been the classic par excellence -with the exception of the Romantic period- is the reason why his translations occupy an outstanding place in the history of Basque literature: the anonymous author of the manuscript Melibeo from the Bonaparte funds, Iturriaga, Miangolarra, Arregi, Ibinagabeitia and Orixe are the makers of this part -by and large the most important one- of the Basque Fortleben of Virgil. The translations of the Eclogues and the Georgics are analyzed in this paper from the perspective imposed by philological scholarship and literary history: on the one hand, we establish the basis first to interpret correctly the aforementioned translations as such and second to locate them properly within these authors' work and, more generally, within the history of Basque literature; on the other hand, we pay especial attention to the peculiarities -indeed remarcable- shown by the influence of Virgil's work in the Basque Country.